The Verbs with the Notion of Eating in Manggaraian Language: Natural Semantic Metalanguage Analysis - Tobias Gunas; Sebastianus Menggo; Yosefina Helenora Jem (RETORIKA: Jurnal Ilmu Bahasa, 2021)
The aim of this research is to explicate and account for the verb of eating in Manggaraian language. There are some verbs denoting the meaning of eating, such as hang, lompong, jumik, mboros, takung, laâ€™ur, alas, pongo muâ€™u. The qualitative research method was applied to unveil and explain the explication of meaning in the given verbs respectively. Field-observation and recording were the techniques used to gather the data from the natural speakers utterances as well as part of the data were based on the researchersâ€™ intuitive knowledge as the native speakers. The data were analyzed through the theory of Natural Semantic Metalanguage (NSM). The results of the analysis reveal that Manggaraian language has the inventory of verbs designating the meaning of eating such as hang, jumik, lompong, mboros, takung, raci, alas, pongo muâ€™u. In terms of semantic prime, the verbs are under the category of the action verb. Comparing to the other verbs, the verbs jumik, lompong, pongo muâ€™u have more delicate meaning of eating. Furthermore, those verbs are classified into generic and specific category of meaning. The verbs â€œhang, jumik, mborosâ€ are generic in meaning while the verbs lompong alas,racik, pongo muâ€™u, takung are specific in meaning. The verbs are categorized into non-compositional polysemy. Regarding the explication of meaning, the verbs reveal the action and the process of eating involving certain parts of body (hands and mouth) as well as specific tools (plate, spoon, bowl).